New Derivative-free Nonmonotone Line Search Methods for Unconstrained Minimization - Nikolovski, Filip; Stojkovska, Irena (My University, 2013)
Two new derivative-free nonmonotone line search methods for unconstrained optimization are proposed and analyzed. Convergence is established under standard conditions. Numerical results show good performance of the proposed methods.
Keywords: unconstrained optimization; nonmonotone line search; derivative-free methods